Allometric coefficient in broilers and development of white striping and wooden breast myopathies - Santos, Fernando Alberto Benitez dos (2023)
The aim was to study the evolution and severity of white striping and wooden breast myopathies and to carry out a study on the parameters of meat quality and allometric growth of male and female broilers at different ages. The experiment was conducted in a broiler house in a completely randomized design, using 960 one-day-old chicks of the Cobb (R) strain, with 480 chicks of each sex. 96 birds per treatment were slaughtered weekly at the age of 21 to 49 days. The present study analyses the occurrence of myopathies, their scores, and their evolution over the age of the birds, comparing males and females. Further assessments included the allometric coefficient and meat quality analyses such as physical measurements (breast length, width, and thickness), pH, colour (L*, a*, and b*), drip loss, water-holding capacity, cooking loss, and shear force. The results demonstrate that the sex of birds did not affect the occurrence of white striping and wooden breast myopathies. However, the degree of myopathies evolved with advancing age, suggesting the weight as a predisposing factor for these myopathies. The emergence of white striping myopathy occurred as early as in the third week of the birds' life. Wooden breast did not develop as isolated myopathy, occurring only in the concomitant presence of white striping. The allometric coefficient demonstrated that regardless of the sex and age, broiler breast had positive heterogonic growth, i.e. late growth in relation to the other parts of the body.